Transnational Crime of Illegal Drug Circulation in Pekanbaru City - Muhammad Zulherawan; Mohamad Fauzi Latib; Rendi Tri Afrianda; Rizki Pratama (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
The circulation of illegal drugs represents one of the forms of transnational crime that seriously impacts public health and consumer protection. This study aims to analyze the dynamics of illegal drug circulation in Pekanbaru City, identify the perpetrators' modus operandi, and evaluate the effectiveness of the Big Post for Drug and Food Supervision (BBPOM) in enforcement actions. The research method employs a qualitative approach with a case study, through analysis of secondary data and documentation from BBPOM, as well as interviews with relevant parties. The results indicate significant fluctuations in the number of cases during 2019–2023, with the highest surge in 2021 at 6,667 cases, dominated by supplies from Asia and Southeast Asia. The perpetrators' modus operandi includes product disguise, digital distribution, and hidden storage to evade supervision. The role of BBPOM, in collaboration with Kominfo, is crucial in enhancing supervision effectiveness, although it still faces challenges in resources and cross-sectoral coordination. This study concludes that eradicating illegal drugs requires a comprehensive strategy that combines repressive efforts, structural prevention, public education, and cross-border cooperation.